Paracoccidioidomicose: estudo radiológico e pulmonar de 58 casos - Campos, E. P.; Padovani, C. R.; Cataneo, A. M. (FapUNIFESP (SciELO), 1991)
Spirometric and haemogasimetric tests were performed in 52 patients with unifocal and multifocal progressive Paracoccidioidomycosis pulmonary diseases, in 5 patients with juvenile and 1 female internal genital forms. The age ranged from 20 to 74 years old and the duration of disease from 3 to 25 years. Dyspnea, cough, tegumentary and lymphatic manifestations were the most predominant signs observed. Fourteen of them was developed Cor pulmonale. Impaired renal function was recorded in 19 patients, cardiac symptoms were described in 7 and hyporeactor adrenal activity was showed in 13 patients. Radiological studies demonstrated mild in 16, moderate in 24 and severe pulmonary lesions types in 18 patients. The pulmonary function revealed: normal spyrographic findings in 17, pure obstructive type in 32 and mixed form in 9 of them. Hyperventilation was described in 54 individuals and all of them showed an increasing of the alveolo-arterial difference. PaO2 less than 80 mm/Hg observed in 36 of them. Statistical analysis demonstrated significative association between clinical evolution and radiological interpretation. Similar data were obtained in radiology evaluations, clinical evolutive studies and pulmonary functions described in these patients. The granulomatous reaction due to Paracoccidioidomycosis, in heavy smokers patients, gave origin to the alterations in small airways predisposing the interalveolar dissemination an impaired alveolo-arterial diffusion.
Paracoccidioidomycosis: radiologic and pulmonary study in 58 cases
Pulmonary and radiological studies in 58 paracoccidioidomycosis patients
Keywords: adult; aged; female; human; lung function test; lung mycosis; male; pathophysiology; radiography; South American blastomycosis; Adult; Aged; English Abstract; Female; Human; Lung Diseases, Fungal; Male; Middle Age; Paracoccidioidomycosis; Respiratory Function Tests